Buying Beauty: On Prices and Returns in the Art Market - Renneboog, Luc; Spaenjers, Christophe (Management Science, 2013)
This paper investigates the price determinants and investment performance of art. We apply a hedonic regression analysis to a new data set of more than one million auction transactions of paintings and works on paper. Based on the resulting price index, we conclude that art has appreciated in value by a moderate 3.97% per year, in real U.S. dollar terms, between 1957 and 2007. This is a performance similar to that of corporate bonds—at much higher risk. A repeat-sales regression on a subset of the data demonstrates the robustness of our index. Next, quantile regressions document larger average price appreciations (and higher volatilities) in more expensive price brackets. We also find variation in historical returns across mediums and movements. Finally, we show that measures of high-income consumer confidence and art market sentiment predict art price trends. This paper was accepted by Wei Xiong, finance.